Python for absolute beginners - Campesato, Oswald (Mercury Learning and Information, 2023)
This book eases you into the foundational aspects of Python 3.x with an extensive range of code samples that illustrate its diverse features. Start with Python tools and installations, and progressively learn intricacies like strings, loops, conditional logic, and much more. The appendices on NumPy and Pandas provide insights into efficient numerical operations, making it a holistic resource for novice programmers. Companion files with code samples are available for downloading from the publisher